INFLUENCE OF MACRONUTRITIENTS INTAKE ON NITROGEN BALANCE IN CRITICALLY ILL PATIENTS - Khan, Safdar Ali; Zahid, Maryam; Naqvi, Shahab; Kirmani, Muzaffar; Zaidi, Sabeen Khurshid; Khalil, Hafsa (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the frequency of positive nitrogen balance in cardiac surgical intensive care unit and correlating with critical illness and to find out the relationship between carbohydrates, protein and fat intake and nitrogen balance. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from 1st July 2014 to Dec 2014. Patient and Methods: Patients selected through purposive convenient sampling from adult intensive care unit of Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi who had undergone any cardiac surgery (CABG or valve replacement). Demographic, clinical and nutritional data was collected. Nitrogen balance was obtained by subracting nitrogen intake with nitrogen output. Results: Out of 46 patients 33% of the patients have nitrogen balance within -2 to +2 (normal range) and 13% of the patients had more than +2 nitrogen balance. Thirty nine patients had SOFA score of <13 of when 49% of the patients had nitrogen balance -2 to +2 and >2 whereas 71% of the patients had with SOFA scores >13 were having negative nitrogen balance. Among patients with nitrogen balance -2 to +2 and > 2, 13 consumed calories > 60% , 81% consumed proteins > 60%, 43% consumed carbohydrates > 60% and 57% consumed fats > 60% Conclusion: According to our study majority of the patients falling in group of nitrogen positive negative balance -2 to +2 (normal range) and >2 were consuming good protein, moderate fat and carbohydrate intake, and had < 50% of the mortality.